The (Un) intended consequences of institutions lowering barriers to entrepreneurship: The impact on female workers. (3rd February 2020) - Castellaneta, Francesco; Conti, Raffaele; Kacperczyk, Aleksandra
Abstract: We propose that institutions that reduce barriers to entrepreneurship lead to intended consequences, increasing entry rate among individuals facing obstacles to entrepreneurship, such as women. But these regulations also have unintended consequences, decreasing the value appropriated by women who stay in paid employment, as these women lose support of their departing peers. Using an exogenous reduction in entry barriers in Portugal between 2005 and 2009, we find that women launch new ventures at higher rates than men, when entry barriers fall, but the same changes lead to a relative decline in women's wages in paid employment. These effects are amplified for women in managerial positions, who benefit if they leave but lose if they stay. Our study contributes to a nuanced understanding of rent‐allocation in firms. Managerial Summary: We study the unintended consequences of lowering barriers to entry—an important institutional change to foster entrepreneurship, especially among those facing strongest entry barriers. We examine the effects of such regulations on women departing to entrepreneurship and those staying in incumbent firms, using the registry data from Portugal. The results show that lowering entry barriers leads to higher rates of entrepreneurial entry among women, as intended. But we also find that this deregulation reform results in a wider gender pay gap among those who stay in incumbent firms. We attribute these increases to reductions in bargaining power and productivity, which result from the departure of socially‐proximate peers. Finally, these intended and unintended consequences are especially common among female managers—who are more likely to leave for entrepreneurship, on the one hand, but also more likely to witness greater pay gaps in wage work, on the other hand.